Influence of Prematch Perceived Wellness on High-Intensity Locomotor Activities of Professional Soccer Players During in-Season Matches - Marqués-Jiménez, D., Quílez-Larrayad, P., & Izquierdo, J. M. (International Journal of Sports Physiology and Performance, 2024)
Purpose: The aim of this study was to determine the influence of prematch perceived wellness on high-intensity locomotor activities of professional soccer players during in-season matches.